Methodology of Teaching English in Higher Educational Institutions Not Related to Philology - G‘ofurova Gulmirahon Mannapovna (International Journal of Scientific Trends, 2023)
This article talks about the methods of teaching English in universities. These teaching methods are more used in practical classes, and have good results.